Penerapan Prosedur, Metode, dan Analisis Terjemahan pada Teks Naratif “The Endless Tale” - Juhariyanti; Misyi Gusthini (HUMAYA Jurnal Hukum Humaniora Masyarakat dan Budaya, 2022)
This research aims to describe the process of translating the narrative text, i.e., “The Endless Tale”, by using Newmark’s model of translation methods and procedures and to analyze its translation. The translation was analyzed by providing annotation on the equivalence selected. The author employed an empirical-based qualitative method in the form of linguistic constituents (e.g., idioms and culture-related words or terms) through three stages, i.e., compiling, collecting, and analyzing the translation. For annotating or explaining idioms or terms in this narrative text, the author used both offline and online dictionaries to produce the most appropriate translation. The problems encountered in the translation process include matching words and sorting phrases or transferring the meaning of idioms in the text into the target language accurately.